Activity and toxicity of intramuscular 1000 iu/m2 polyethylene glycol‐E. coli L‐asparaginase in the UKALL 2003 and UKALL 2011 clinical trials. (29th March 2022) - Sidhu, Jasmeet; Masurekar, Ashish Narayan; Gogoi, Manash Pratim; Fong, Caroline; Ioannou, Tasos; Lodhi, Taha; Parker, Catriona; Liu, Jizhong; Kirkwood, Amy A.; Moorman, Anthony V.; Das, Kiranmoy; Goulden, Nicholas J.; et al.
Summary: In successive UK clinical trials (UKALL 2003, UKALL 2011) for paediatric acute lymphoblastic leukaemia (ALL), polyethylene glycol‐conjugated E. coli L‐asparaginase (PEG‐EcASNase) 1000 iu/m 2 was administered intramuscularly with risk‐stratified treatment. In induction, patients received two PEG‐EcASNase doses, 14 days apart. Post‐induction, non‐high‐risk patients (Regimens A, B) received 1–2 doses in delayed intensification (DI) while high‐risk Regimen C patients received 6–10 PEG‐EcASNase doses, including two in DI. Trial substudies monitored asparaginase (ASNase) activity, ASNase‐related toxicity and ASNase‐associated antibodies (total, 1112 patients). Median (interquartile range) trough plasma ASNase activity (14 ± 2 days post dose) following first and second induction doses and first DI dose was respectively 217 iu/l (144–307 iu/l), 265 iu/l (165–401 iu/l) and 292 iu/l (194–386 iu/l); 15% (138/910) samples showed subthreshold ASNase activity (<100 iu/l) at any trough time point. Older age was associated with lower (regression coefficient −9.5; p  < 0.0001) and DI time point with higher ASNase activity (regression coefficient 29.9; p  < 0.0001). Clinical hypersensitivity was observed in 3.8% (UKALL 2003) and 6% (UKALL 2011) of patients, and in 90% or more in Regimen C. A 7% (10/149) silent inactivation rate was observed in UKALL 2003. PEG‐EcASNase schedule in UKALL paediatric trials is associated with low toxicity but wide interpatient variability. Therapeutic drug monitoring potentially permits optimisation through individualised asparaginase dosing.